Fibrinolytic Response to Venous Occlusion Compared to Physical Stress Test in Young Patients with Coronary Artery Disease - Nikfardjam, Mariam; Graf, Senta; Beckmann, Renate; Hornykewycz, Stephan; Koller-Strametz, Jeanette; Binder, Bernd R.; Huber, Kurt (Thrombosis and Haemostasis, 1999)
Introduction: Venous occlusion (VO) and exercise stress (ES) are stimulators of the fibrinolytic system. Aim of this study was to answer which of both stimulation tests is more useful in patients with symptom-limited coronary artery disease (CAD) to evaluate possible defects in the fibrinolytic system.Methods and results: We investigated 20 patients (M/F = 15/5; mean age = 36.7 years) with angiographically proven CAD for their plasma levels of tissue-type plasminogen activator (t-PA) and plasminogen activator inhibitor-type-1 (PAI-1) at basal conditions as well as after VO and at maximal ES (standardised bicycle stress test) and compared the data to those obtained from 12 sex- and age-matched healthy controls (M/F = 9/3; mean age = 40.4 years). At basal conditions mean t-PA activity and t-PA antigen plasma levels were within the normal range and comparable between the two study groups. After both VO and maximal ES, mean t-PA activity and t-PA antigen levels increased significantly more in the control group as compared to the CAD group. Mean PAI-1 activity plasma levels were significantly higher in the CAD group at basal conditions before VO (patients 7.0 ± 3.1; controls 3.9 ± 3.9; IU/ml; p = 0.025) as well as before ES (patients 8.1 ± 3.5; controls 4.3 ± 3.8; IU/ml; p = 0.009). PAI-1 activity plasma levels showed a significant decrease for patients and controls only after VO, while PAI-1 activity was not significantly decreased in both study groups at maximal ES.Discussion: The significantly higher increase in mean plasma levels of t-PA activity and t-PA antigen after VO compared to ES in both groups might be explained by the fact that CAD induced symptoms in the patients during ES thus permitting only 80% of their age, sex, and body mass index related optimal work load.Conclusion: VO and ES are applicable triggers of the endogenous fibrinolytic system in healthy subjects and patients who are not limited in their physical exercise. Standardised VO appears to be superior to ES as stimulation test of the endogenous fibrinolytic system in patients with symptomatic CAD.
Keywords: Coronary artery disease; fibrinolytic system; venous occlusion; physical stress test